2007
DOI: 10.1021/cm070512d
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Azobenzene-Based Materials for Optical Generation of Microstructures

Abstract: We propose a concept of supramolecular materials for effective all-optical generation of surface relief structures and optical anisotropy. The materials are based on the ionic interactions between photochromic azobenzene units and polyelectrolytes. The materials are easy to produce and they allow the inscription of the 1.8 µm deep surface relief gratings. Moreover, the induced structures were thermally very stable. Both distinctive features of the new materials, namely, the dynamic behavior of molecular orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
107
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(112 citation statements)
references
References 39 publications
0
107
1
Order By: Relevance
“…9. 129 They also demonstrated that crosslinked polysiloxane networks ionically complexed to azobenzenes resulted in efficient SRG formation and consideration of the optimal rigidity of the material (tailored by varying the degree of cross-linking) was discussed. 131 By using conceptually similar polyelectrolyte-azobenzene complexes as in ref.…”
Section: Photoinduced Surface Patterningmentioning
confidence: 99%
See 2 more Smart Citations
“…9. 129 They also demonstrated that crosslinked polysiloxane networks ionically complexed to azobenzenes resulted in efficient SRG formation and consideration of the optimal rigidity of the material (tailored by varying the degree of cross-linking) was discussed. 131 By using conceptually similar polyelectrolyte-azobenzene complexes as in ref.…”
Section: Photoinduced Surface Patterningmentioning
confidence: 99%
“…131 By using conceptually similar polyelectrolyte-azobenzene complexes as in ref. 129, which were spin-coated on substrates containing plasmonic gold nano-antennas, the imprint of the plasmonic near field could be inscribed onto the polymer surface. 132 The authors also noted that the polymer-azobenzene complexes were sensitive to humidity due to their highly charged nature.…”
Section: Photoinduced Surface Patterningmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Stumpe and co-workers found that the grating formation when utilizing sol-gel techniques is greatly influenced by multiple factors such as cross-linking and plasticizing effects [60]. They also proposed a different ionic supramolecular azobenzene-based material [61]. This ionic material allows for the creation of deep modulation depths (i.e., 1.8 µm) while being thermally stable up to 150 • C due to its strong ionic interactions.…”
Section: Light-induced Permanent Surface Relief Gratings In Linear Azmentioning
confidence: 99%
“…[12] Azobenzenes can furthermore be readily integrated into complex self-assembled architectures through non-covalent interactions, specifically ionic [13a,b] and hydrogen-bonding, [13c] providing routes to exciting new responsive materials. [14] It has since been shown that efficient SRGs can also be inscribed in both ionic [15] and hydrogen-bonded supramolecular homopolymer-azobenzene complexes. [16] Seki et al showed, [17] for the case of a random copolymer, that non-covalent functionalization enables selective removal of the azobenzene chromophores after the SRG inscription, although their approach led to severe degradation of the SRG structure.…”
Section: Doi: 101002/adma201103793mentioning
confidence: 99%